Erratum to: The Changing Epidemiology of HIVAssociated Adult Meningitis, Uganda 2015–2017 - Ellis, Jayne; Bangdiwala, Ananta S.; Cresswell, Fiona V.; Rhein, Joshua; Nuwagira, Edwin; Ssebambulidde, Kenneth; Tugume, Lillian; Rajasingham, Radha; Bridge, Sarah C.; Muzoora, Conrad; Meya, David B.; Boulware, David R. (Open Forum Infectious Diseases, 2019)
An error appeared in an article published in the September 2019 issue: The Changing Epidemiology of HIV-Associated Adult Meningitis, Uganda 2015–2017. Open Forum Infect Dis. 2019 Sep 29;6(10):ofz419. doi: 10.1093/ofid/ofz419. eCollection 2019 Oct. In the methods section it stated that the Biofire multiplex polymerase chain reaction panel tested for HHV6 and HHV7. This was incorrect, as the panel only includes HHV6. This has now been corrected online
Keywords: HIV-Associated; Adult Meningitis; Uganda